2022
DOI: 10.3390/ijms23042302
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium Supplementation Accelerate Vascular Calcification in a Model of Pseudoxanthoma Elasticum

Abstract: Arterial calcification is a common feature of pseudoxanthoma elasticum (PXE), a disease characterized by ABCC6 mutations, inducing a deficiency in pyrophosphate, a key inhibitor of calcium phosphate crystallization in arteries. Methods: we analyzed whether long-term exposure of Abcc6−/− mice (a murine model of PXE) to a mild vitamin D supplementation, with or without calcium, would impact the development of vascular calcification. Eight groups of mice (including Abcc6−/− and wild-type) received vitamin D suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…An increasing amount of evidence demonstrates that optical photothermal infrared (OPTIR) microspectroscopy is a valuable imaging and spectroscopy tool that can extract chemical information about biomolecules directly from individual cells and tissues at submicron resolution. OPTIR is a novel infrared spectromicroscopy technique that exploits the photothermal effect . Specifically, infrared (IR) absorption induces a photothermal response consisting of thermal expansion and a change in the index of refraction of the sample, which leads to an intensity change of the probe light and allows the detection of the photothermal response.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing amount of evidence demonstrates that optical photothermal infrared (OPTIR) microspectroscopy is a valuable imaging and spectroscopy tool that can extract chemical information about biomolecules directly from individual cells and tissues at submicron resolution. OPTIR is a novel infrared spectromicroscopy technique that exploits the photothermal effect . Specifically, infrared (IR) absorption induces a photothermal response consisting of thermal expansion and a change in the index of refraction of the sample, which leads to an intensity change of the probe light and allows the detection of the photothermal response.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study by Young et al suggested that serum vitamin D deficiency may contribute to the progression of coronary calcification [ 28 ]. In addition, Bouderlique et al revealed that vascular calcification was accelerated in a murine model of pseudoxanthoma elasticum when vitamin D or calcium supplements were added [ 29 ]. When the serum vitamin D level is at the right concentration, it can inhibit the abovementioned process and slow the progression of AAC.…”
Section: Discussionmentioning
confidence: 99%
“…We have already investigated biological samples from different organs and parts of the human body, namely kidney [177][178][179][180][181][182][183], prostate [184,185], breast [13,103], thyroid [104][105][106], cartilage [186][187][188][189][190][191][192][193], bone [194][195][196][197], tooth [198], pancreas [199], skin and hairs [53][54][55]147,165,168,[200][201][202][203] and cardiovascular system [140,204,205]. We have also investigated cells [206], mice [207][208][209][210], and medical devices [211,212], as well as chemical compounds identified in k...…”
Section: Characterization By Physicochemical Techniquesmentioning
confidence: 99%